An investigation on the relation between learning motivation and academic performance on Malaysian University Student's mandarin learning - Lee Hui Ling (2012)
Owing to rising of the status of Malaysia, the number of Mandarin learner has been increasing dramatically. The subject that Chinese as a second language is highly valued by most of the Malaysian. On the studies of third language learning, motivation is a key influential factor with students’ academic performance. Therefore, it is significant to make a multi-perspective research on the motivation of the learners in Teaching Chinese as a Foreign Language (TCFL) theoretically and practically. On the basis of the relevant research findings in the field of TCFL, this study is a comprehensive survey and analysis of the learning motivation of Malaysian University Students, adopting many research methods such as questionnaire, classroom observation, interviews and so on. The participants are 75 students who are studying Mandarin (level 2) in University of Malaysia Kelantan (UMK). The results on students’ Mandarin learning will be analyzed by the software SPSS. The purpose of this study is: (1) to let the Malaysian University Students have a much clearer awareness of their motivation; and (2) to exam the relationship between learning motivation and academic performance on Mandarin Learning. Therefore, in the process of Chinese teaching, teachers should make a concrete analysis of specific issues and stimulate their leaning motivation appropriately so as to produce better learning outcomes and teaching effect. At the same time, we have put forward concrete teaching strategies for stimulating the Malaysian Chinese learners’ motivation on the basis of their learning conditions.